MALAYSIAN 10 YEARS TECHNOLOGY EXPENDITURE - Noreen Balqis Muhammad; Irdhina Sofina Shahrin; Nur Fara Syahadha Anuar; Asmaa’ Aqilah Mohd Rosli; Nurhanis Nabiha Md Osman; Fuadah Johari (IQTISHADUNA, 2022)
This paper studies and observes Malaysian ten years of technology expenditure. The analysis of Malaysia's technological growth over ten years is one of the topics covered in this discussion. In addition, factors that contribute to the state of technology are now an important problem in this working paper and discussed how to solve problems arising from Islamic perspectives. This is because, as knowledgeable Muslims, we need to be sensitive and efficient in developing the economy. Not only that, but we are also responsible for declaring that not from a technological point of view alone needs to be taken heavily on the contrary from other aspects, such as commerce that gets a boost in Islam needs to be emphasised. This is to form a community or a developed country along with the development of the world today.